Os mecanismos de participação social direta na democracia brasileira - Soistak, Jonas (2015)
This research has the objective to analyze the function of the mechanisms of direct social participation in the Federal Constitution of 1988 in the face of the contested legitimacy crisis of representative democracy. The method of approaching used in the most prevalent form was the deductive and the method of procedure was used the comparative method. The methodological procedures employed were a bibliographical research and a documentary research and we chose a qualitative approach to the problem. The first chapter develops a historical study of the categories of democracy and representation, describing the historical aspects and the presenting the development of theories on the subject. The second chapter discusses the evolution of our Constitution and the Brazilian democracy, in order to enable a better comprehension of the current model and difficulties. The third chapter discusses the possible existence of a crisis of legitimacy of democracy and the role that the mechanisms of direct social participation can exercise to reverse or mitigate the effects of this scenario. The fourth chapter examines each of the instruments of direct social participation in the Federal Constitution of 1988 in an analysis of the constitutional and infra-constitutional devices, identifying the main difficulties created by the Constitution and the law that has obstructed the widespread use of participatory tools. At this point, we ponder on the possible changes for the improvement of these mechanisms, what means we discuss the changes of applicable alternatives and the adoption of a revocation mechanism of the mandates of representatives in Brazil. The research thereby develops itself to verify the hypothesis that the expansion and the realization of participatory democracy can contribute to a reduction of the problems encountered in the current Brazilian political system that lead to a confidence and legitimacy crisis in representative democracy. Furthermore, the research advances in the defense of appreciation of participatory democracy through the use of mechanisms of direct social participation.